Internal hernia and caecal volvulus secondary to adhesion at inguinal preperitoneal mesh - Tani, Daniel; Sivasuthan, Goutham; Ndegwa, Reuben; Mansour, Omar (International Surgery Journal, 2022)
We reported the case of a caecal volvulus in a 52-year-old female which appeared to result from a dense intra-abdominal adhesion from a previous inguinal hernia repair. The patient presented with upper abdominal pain and obstructive symptoms. Computed tomography revealed the caecum in a whirlpool appearance characteristic of a volvulus, and there was resulting proximal bowel dilatation suggesting obstruction. The patient had previously undergone a laparoscopic right inguinal hernia repair 9 years prior to presentation in addition to a hernia repair on the contralateral side, and a left sided Spigelian hernia repair. She was managed operatively with exploratory laparoscopy. Her right iliac fossa had scarring at the peritoneum consistent with an inguinal hernia mesh with no intra-abdominal breach. There was a band adhesion originating from this region, directly posterior to the scarring, with the caecum wrapping around the adhesion and causing an obstruction. The internal hernia was reduced, a right hemicolectomy performed, and the patient successfully discharged after six days. Adhesion formation following inguinal hernia repairs are not a well-documented complication. In this case, there was an obvious adhesion that acted as the fulcrum for a caecal volvulus and clearly originated on the abdominal wall directly behind the previous inguinal hernia mesh suggesting that the hernia repair may have instigated the adhesion. Whilst rare, adhesion formation may need to be a consideration in inguinal hernia mesh repairs.